Bản tổng hợp, giải trình, tiếp thu ý kiến góp ý đối với dự án Luật Công chứng (sửa đổi) - Bộ Tư pháp (2024)
Toàn văn Bản tổng hợp, giải trình, tiếp thu ý kiến góp ý đối với dự án Luật Công chứng (sửa đổi).